Facile Synthesis of Fe‐Doped CoO Nanotubes as High‐Efficient Electrocatalysts for Oxygen Evolution Reaction. Issue 4 (14th February 2022) - Tang, Fan; Guo, Sijie; Sun, Yonggang; Lin, Xijie; Qiu, Jianhua; Cao, Anmin
Abstract : Developing high‐performance, low‐cost, and robust electrocatalysts is of great importance to boost the efficiency of oxygen evolution reaction (OER). Herein, based on the integrated design of chemical composition and geometric structure, Fe‐doped CoO nanotubes (NTs) with high OER activity are prepared by a facile template‐free approach. The construction of this tubular structure is realized via a simple wet‐chemical reaction to prepare solid nanorods as precursor and a subsequent calcination treatment of the precursor to form hollow cavity. The favorable composition and unique hollow structure endow these Fe‐doped CoO NTs with remarkable activity toward OER. When used as the electrocatalyst for OER, the Fe‐doped CoO NTs show a small overpotential of 282 mV at the current density of 10 mA cm −2, a low Tafel slope of 78.26 mV dec −1, and a high turnover frequency of 0.0965 s −1 at the overpotential of 282 mV, which is superior to those of CoO NTs and solid CoO nanoparticles. Moreover, the Fe‐doped CoO NTs also exhibit excellent long‐term stability of 24 h at the current density of 10 mA cm −2 . Abstract : A facile and controllable template‐free synthetic protocol is developed to prepare Fe‐doped CoO nanotubes (NTs) as high‐performance electrocatalysts for oxygen evolution reaction (OER). Contributing to the unique hollow tubular structure and the synergistic effect between Fe and Co, the as‐prepared Fe‐doped CoO NTs exhibit superior OER activity to CoO NTs and CoO nanoparticles.